Effectiveness of a Child Abuse Prevention Training Program on the Tendency Towards Child Abuse and Parental Self-Efficacy in Mothers with a History of Child Abuse - Moradi, Mahmood; Yousefi, Zahra; Bahramipour, Mansoureh (Psychology of Woman Journal, 2023)
Objective: This research aimed to investigate the effectiveness of a child abuse prevention training method on the tendency towards child abuse and parental self-efficacy in mothers with a history of committing child abuse in the city of Isfahan. Methods and Materials: This applied research was of a quasi-experimental type, conducted with a pre-test, post-test, and a 2-month follow-up with a control group. The population in this study included all clients of the social emergency centers in Isfahan in the year 2023, from which 30 mothers with a history of child abuse interested in participating were selected using purposive sampling and randomly assigned to experimental and control groups. Participants from both groups completed the Child Abuse Tendency (CAT) and Parental Self-Efficacy (PSE) questionnaires at the pre-test, post-test, and two-month follow-up stages. The experimental group received eight 90-minute sessions of child abuse prevention training. Data were analyzed using SPSS version 26 and the repeated measures analysis of variance method. Findings: The results of the repeated measures analysis of variance indicated that child abuse prevention training effectively reduces the tendency towards child abuse (F=28.45) and also increases the self-efficacy (F=55.73) of mothers with a history of child abuse (P<0.05). Conclusion: Based on the results, it can be said that to reduce the tendency towards child abuse and improve the self-efficacy of mothers with a history of child abuse, the child abuse prevention training method can be used.